Tempeh source of vegetable protein: nutritional composition and health benefits - Gullian Klanian, Mariel; Osorio Di Gianluca, Silvana (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2024)
Tempeh is a food native to Indonesia obtained from the controlled fermentation of soybeans by the fungus Rhizopus oligosporus. This Southeast Asian food is increasingly becoming an inexpensive substitute for meat due to its excellent nutritional profile. This review presents the most relevant aspects of the history of tempeh, the current regulation and explains the changes in soybeans' nutritional composition after the enzymatic action of the fungus. The review describes the nutritional composition and the health benefits derived from its consumption.